2009
DOI: 10.1002/ar.21000
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Blood‐Spleen Barrier in the Soft‐Shelled Turtle, Pelodiseus Sinensis

Abstract: The soft‐shelled turtle, Pelodiseus sinensis, and its spleen section showing carbon particles of injected Indian ink mainly in the ellipsoid which composed the blood‐spleen barrier. See Bao et al, on page 1079, in this issue. Anatomical Record 292:1079–1087.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…PELS structures have previously been reported in poultry and reptiles that do not have an MZ structure. Ellipsoid and PELS structures replace the MZ function as blood spleen barrier, in animals that do not possess MZ structure (Bao, Li, Wang, Qin, & Xu, ; Neely & Flajnik, ; Sun et al, ; Udroiu & Sgura, ; Zhang et al, ). No previous studies have been reported concerning the existence of PELS structures in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…PELS structures have previously been reported in poultry and reptiles that do not have an MZ structure. Ellipsoid and PELS structures replace the MZ function as blood spleen barrier, in animals that do not possess MZ structure (Bao, Li, Wang, Qin, & Xu, ; Neely & Flajnik, ; Sun et al, ; Udroiu & Sgura, ; Zhang et al, ). No previous studies have been reported concerning the existence of PELS structures in mammals.…”
Section: Discussionmentioning
confidence: 99%